UMPSA excels at ISPE Singapore Hackathon 2025 - muhammad nur aqmal, nazri (UMPSA, 2025)
SINGAPORE, 28 August 2025 - UMPSA students showcased their talent at the ISPE Singapore Hackathon 2025, held on 27-28 August at the Suntec Convention & Exhibition Centre, Singapore.